Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Perhubungan (Dishub) Kabupaten Karawang - Diella Fakhirah Yunansyah; Anggi Pasca Arnu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the partial or simultaneous effect of organizational culture, employee work discipline on the performance of the employees of the Department of Transportation (Dishub) Karawang Regency. The method used is descriptive and verification method. The population in this study amounted to 255 employees of the Department of Transportation Karawang Regency. The sample in this study amounted to 153 employees using the Solvin method. The sampling technique in this study used a simple random sampling technique. The results showed that there was a partial influence of 34.6% between Organizational Culture on employee performance and there was a partial influence between work discipline on employee performance of 23.6%. While the simultaneous influence of organizational culture and work discipline on employee performance is 58.2% and the influence of other variables outside the model is 41.8%. In conclusion, there is a significant influence between Organizational Culture, Work Discipline, and simultaneously Organizational Culture and Work Discipline on the Performance of the Employees of the Department of Transportation (DISHUB) Karawang Regency. Keywords: Organizational Culture, Work Discipline, Employee Performance